Non‐technical skills of surgical trainees and experienced surgeons. Issue 6 (13th March 2017) - Gostlow, H.; Marlow, N.; Thomas, M. J. W.; Hewett, P. J.; Kiermeier, A.; Babidge, W.; Altree, M.; Pena, G.; Maddern, G.
Abstract : Background: In addition to technical expertise, surgical competence requires effective non‐technical skills to ensure patient safety and maintenance of standards. Recently the Royal Australasian College of Surgeons implemented a new Surgical Education and Training (SET) curriculum that incorporated non‐technical skills considered essential for a competent surgeon. This study sought to compare the non‐technical skills of experienced surgeons who completed their training before the introduction of SET with the non‐technical skills of more recent trainees. Methods: Surgical trainees and experienced surgeons undertook a simulated scenario designed to challenge their non‐technical skills. Scenarios were video recorded and participants were assessed using the Non‐Technical Skills for Surgeons (NOTSS) scoring system. Participants were divided into subgroups according to years of experience and their NOTSS scores were compared. Results: For most NOTSS elements, mean scores increased initially, peaking around the time of Fellowship, before decreasing roughly linearly over time. There was a significant downward trend in score with increasing years since being awarded Fellowship for six of the 12 NOTSS elements: considering options (score −0·015 units per year), implementing and reviewing decisions (−0·020 per year), establishing a shared understanding (−0·014 per year), setting and maintaining standards (−0·024 per year), supporting others (−0·031 per year) and coping with pressure (−0·015 per year). Conclusion: The drop in NOTSS score was unexpected and highlights that even experienced surgeons are not immune to deficiencies in non‐technical skills. Consideration should be given to continuing professional development programmes focusing on non‐technical skills, regardless of the level of professional experience. Abstract : Rise and fall